Iceland : Report on Observance of Standards and Codes (ROSC). (IMF Staff Country Reports; Country Report, 2014)
This Report on Observance of Standards and Codes on Iceland summarizes the findings and recommendations of the assessment. This assessment of the current state of the implementation of the Basel Core Principles for Effective Banking Supervision in Iceland has been completed as a stand-alone Report on the Observance of Standards and Codes undertaken by the IMF during March of 2014 at the request of the Icelandic authorities. It is advised to ensure planned legislative amendments clarify the roles regarding banking supervision of liquidity risk, including corrective action. Ensure planned legislative amendments clarify Financial Supervisory Authority in Iceland (FME) actions in the enforcement of buffers. It is also recommended to amend processes, systems and practices in order to use the full definition of qualified holder, beyond the mere quantitative thresholds. The assessment also recommends developing rules and guidelines for banks on the benchmarks, standards, and procedures that the FME will follow in determining the adequacy of bank's risk management and governance systems.